2015
DOI: 10.1074/jbc.m115.674671
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine Modulates T Cell Differentiation through Down-regulating N-Linked Glycosylation of CD25

Abstract: Background:Glucosamine is an amino sugar that has immunoregulatory effects on T cell-mediated diseases. Results: Glucosamine inhibits Th1, Th2, iTreg cells, but promotes Th17 cell development through interference with N-glycosylation of CD25. Conclusion: Glucosamine modulates T cell differentiation in vivo and subsequently influences the progression and severity of autoimmune diseases. Significance: Glucosamine-mediated modulation of CD25 glycosylation can be beneficial to controlling autoimmune diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 60 publications
1
37
0
Order By: Relevance
“…N‐glycan branching on T cells has been implicated in the development of type 1 diabetes, and N‐glycan branching on glucose transporter has been implicated in the development of type 2 diabetes . Both discoveries include N‐glycan interactions with lectins, which are disrupted upon inhibition of the proper protein N‐glycosylation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…N‐glycan branching on T cells has been implicated in the development of type 1 diabetes, and N‐glycan branching on glucose transporter has been implicated in the development of type 2 diabetes . Both discoveries include N‐glycan interactions with lectins, which are disrupted upon inhibition of the proper protein N‐glycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that it is possible to distinguish individuals with different types of diabetes based on their N-glycome data, as it is the case for the HNF1A-MODY and its differentiation from other common and rare types of diabetes [38,42]. N-glycan branching on T cells has been implicated in the development of type 1 diabetes, and N-glycan branching on glucose transporter has been implicated in the development of type 2 diabetes [23,43,44,73,105]. Both discoveries include N-glycan interactions with lectins, which are disrupted upon inhibition of the proper protein N-glycosylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could occur also through metabolites produced by the fungus itself during challenge, with S. cerevisiae strains behaving differently according to the different adaptation to the environment from which they were isolated. It was previously demonstrated that C. albicans can actively shift the balance of tryptophan metabolism in the host through soluble factors (48), and a recent study revealed the glucosamine modulatory properties on T cells (13). Indeed, fungus metabolites could somehow allow for the epigenetic changes that then form the basis for the training event.…”
Section: Discussionmentioning
confidence: 99%
“…Other intrinsic factors including signaling molecules and miRNA have been shown to control signaling in model systems [10, 11]. Extrinsically, metabolic factors and secreted receptors [1214] regulate IL-2R signaling in other disease settings. In this study, we examine IL-2 responsiveness in 98 T1D subjects and 95 healthy controls and explore underlying mechanisms in Teff Our results demonstrate that disease impacts IL-2/IL-2R signaling most prominently in the CD4 Teff compartment.…”
Section: Introductionmentioning
confidence: 99%